Розробка шляхів реформування систем централізованого теплопостачання України - Ширяєва, Наталя Володимирівна; Білоцерківський, Олександр Борисович (НТУ "ХПІ", 2015)
Пропонуються шляхи реформування систем централізованого теплопостачання великих міст України. Досліджено сучасний стан теплоенергетичної галузі України. Наголошено, що в Україні витрати теплоти на опалення об’єктів в 2-3 рази більші, ніж в країнах Західної Європи. Рекомендується для реформування СЦТ розробити та провести організаційні, те хнологічні, нормативно-правовізаходи; удосконалити управління фінансами, перейти до якісно нових методів регулювання тарифних відносин між виробником і споживачем теплоенергії та інші заходи. Зроблено висновки на основі отриманих результатів.

Reforming ways of central heating systems (CHS) in big cities of Ukraine are considered. Current situation in energy industry is analyzed. It was noted that latent heat input on heating in Ukraine is two or three times higher than in Western Europe countries. It was recommended to develop and organize some technology, organizational, and law actions for better work of CHS. Management of finance is also needed an imp rovement. One of the ways is to follow the new quality methods of tariff regulation between producer and supplier of heating energy. On the base of the results some conclusions are made. Analysis of some research results was conducted by A. Havrikova. In the case of two-rate tariff, the payment system is more economically feasible for all the heat market participants. Thus, the rates should progressively increase. The use of economic and mathematical models in practice of thermal power companies will determine optimal rate of energy resources consumption. This will lead companies to maximum profit. Commissioning of new CHS based on combined heat and power energy are also recommended.
Development of reforming ways for central heating systems of Ukraine
Keywords: теплові мережі; економіко-математичні моделі; когенерація; відновлювані джерела енергії; renewable energy sources; heat networks; cogeneration